KAJIAN KONDISI EKSISTING RENCANA PETERNAKAN SAPI DI DESA LAILANJANG, KECAMATAN RINDI, KABUPATEN SUMBA TIMUR, PROPINSI NTT - Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2020)
Food is a basic need for humans to be able to sustain life and therefore adequate food for everyone at all times is a human right that deserves to be fulfilled. Therefore, a massive, radical and revolutionary effort is needed. This shows how important food is. Disruption of food security can trigger various upheavals and potentially endanger national stability. Livestock is a very important sector in producing food products. The livestock industry produces food sources in the form of animal protein that has a high nutritional content, such as beef, chicken meat, eggs, and milk. The condition of livestock which is currently still not developed and there are still many problems from upstream to downstream have caused Indonesia's dependence to import from other countries to meet the food needs. This research was conducted in September 2017 in the area of ​​the planned ranch development in Lailanjang Village, Rindi District, East Sumba Regency, East Nusa Tenggara Province. The plan to develop a cattle farm owned by Asiabeef Biofarm Indonesia in Lailanjang Village, Rindi District, East Sumba Regency, East Nusa Tenggara Province Protected forest area, has an area of ​​± 500 ha which includes grazing areas and other supporting structures. Communities around the planned area for cattle farming need real action in the form of increasing human resources and empowering the community through plasma core programs, the formation of fostered farmer groups and the construction of public facilities needed by the surrounding community. According to the results of the study on the impact of direct and indirect losses from the cattle farm development plan owned by Asiabeef Biofarm Indonesia in Lailanjang Village, Rindi District, East Sumba Regency, East Nusa Tenggara Province Province, in terms of ecology, is very small considering the location is a stretch of grass (savanna) where fires occur almost every year intentionally to get new grass as community animal feed that is released in the area. the. The condition of the location in the planned area for cattle farming development of PT. Asiabeef Biofarm Indonesia in Lailanjang Village, Rindi District, East Sumba Regency, East Nusa Tenggara Province is not a primary natural forest because there are already activities in the forest area such as cattle grazing along with buildings for livestock guards and village roads that connect other villages that can be passed by vehicles four or more wheels. Vegetation/coverage in the planned area of ​​cattle farm development owned by PT. Asiabeef Biofarm Indonesia in Lailanjang Village, Rindi District, East Sumba Regency, East Nusa Tenggara Province, dominated by weeds Imperata cylindrica Raeusch, grass Cyperus rotundus, and gum-lac trees (Schleichera oleosa)